Innovative Learning Strategies to Boost Students' Multimedia Design Skills (International Journal of Engineering and Computer Science, 2025)
The advancement of digital technology requires students to have strong multimedia design skills. The selection of the right learning model is believed to play an essential role in developing these competencies. This study aims to determine the effect of learning models on students' multimedia design skills. A quantitative approach with a quasi-experimental design was used, involving a pretest and post-test to measure students' abilities before and after the implementation of specific learning models. Statistical tests were analyzed to identify the significance of learning outcome differences. The results showed a significant improvement in students' multimedia design skills after applying active learning strategies. Students in the experimental group, who experienced an integration of Problem-Based Learning and Flipped Learning, achieved a mean score of 74.33, while the control group scored 59.72. The t-test confirmed a significant difference between the groups (t = 3.007; p = 0.003), indicating the effectiveness of the active learning model. The project-based approach significantly enhances students' technical skills and creativity in multimedia design. This finding emphasizes the need for educators in higher education to adopt innovative, technology-based learning strategies to build students' digital competencies. Future studies are recommended to explore long-term impacts across diverse disciplines and institutional contexts